Self-assembled bio-derived microporous nanosheet from phytic acid as efficient intumescent flame retardant for polylactide. (September 2021) - Yang, Wenxue; Zhang, Haijun; Hu, Xiaoping; Liu, Yingru; Zhang, Suhua; Xie, Changqiong
Highlights: A novel bio-based mono-component intumescent flame retardant (HACP-PA) was successfully synthesized. The microporous nanosheet was fabricated by template-free self-assembly. HACP-PA provides a higher contact area and interfacial affinity towards uniform dispersion of HACP-PA in PLA matrix. Introducing HACP-PA promotes heterogeneous nucleation and improves the crystallinity of PLA. HACP-PA shows excellent fire retardancy in PLA owing to the formation of a high-quality char layer. Abstract: The design of flame retardants based on environment-friendly perspective is an increasingly promising strategy to meet the requirements of sustainable development. Herein, combining with the advantages of sustainability and high thermal stability of phytic acid and phosphazene, a novel mono-component intumescent flame retardant hexakis (4-aminophenoxy) cyclotriphosphazene-phytic acid with microporous nanosheet morphology (HACP-PA) is synthesized via template-free self-assembly, which assembles carbon source, acid source and gas source into one molecular structure. The fire retardancy of HACP-PA was evaluated by UL-94, limiting oxygen index (LOI), and cone calorimeter. With 5 wt% HACP-PA loading into PLA, the UL-94 V-0 rating was achieved, and the LOI value increased to 24.2%. Compared with PLA, the addition of 5 wt% HACP-PA resulted in 21.5% and 15.3% reductions in the total heat release (THR) and the peak heat release rate (pHRR) of PLA composites, respectively. Moreover, the total smoke production (TSP) also significantly decreased by 31.0%, and the combustible volatile products are remarkably reduced by the incorporation of HACP-PA. This work provides an effective approach to improve the fire-retarding performance and crystallization performance of PLA by introducing sustainable bio-based intumescent flame retardant with a unique nanosheet structure. Graphical abstract: A novel intumescent flame retardant with 2D nanosheets and microporous structure was successfully synthesized through self-assembly to improve the fire retardancy and crystallinity of polylactide. Image, graphical abstract